ANALISIS PENDAPATAN DAN SKALA EKONOMI USAHATANI BAWANG MERAH DI KOTA METRO - Gesti Verdayanti; Muhammad Irfan Affandi; Ani Suryani (Lampung University, 2020)
This research aims to determine the analyze cost, revenue, income and economic of scale of onion farming. This research was conducted in Metro City which is chosen purposively in which total number of respondents are 33 farmers who are chosen using saturation sampling. Primary and secondary data were collected in November 2017–Mei 2018. The research data are analyzed byincome analysis and multiple linear regression analysis with Cobb-Douglass production function. The results of this research showed that onion farming at first cultivation season and second cultivation season was profitable for farmers in Metro City, R/C value of total cost was about 1.43 and 1.53. Economic of scale of onion farming in Metro City was increasing return to scale,meaningthat there was an increase of the profit caused by an increase of total production.Keywords: economic of scale,income,onion farming